J-ALEX trial will crown alectinib as the standard choice for anaplastic lymphoma kinase positive untreated non-small cell lung cancer patients? - Gridelli, Cesare; Casaluce, Francesca; Sgambato, Assunta; Palazzolo, Giovanni; Maione, Paolo (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
About 4–5% of advanced non-small cell lung cancer (NSCLC) patients are diagnosed with an oncogene- addicted disease, due to the presence of echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase (EML4-ALK) fusion gene (1). Before August 2011, chemotherapy was the only option for those patients.